Anti submarine Warfare Oceanography - Shenoy, S. Kedarnath; Sanilkumar, K.V. (Defence Science Journal, 2019)
Anti-submarine warfare (ASW) Oceanography has become an important and independent discipline, especially after World War II as the threat perceptions from hostile underwater platforms has been on a continuously rising trajectory worldwide. There is no doubt that till date, acoustic energy remains the only viable and most effective means to detect underwater objects. However, sound waves are highly susceptible to refraction, reflection, scattering, reverberation and absorption in the ocean medium. Among these, refraction is controlled by the 3D sound speed structure in the specific ocean region and reflection loss by the sea state and ocean bottom characteristics. Water quality parameters such as sediment concentration and suspended biological masses influence attenuation, scattering, reverberation and absorption. Oceanographic variability emerges from diurnal heating, seasonal changes, river discharges, etc. and are the most important environmental factors deciding the 3D sound speed structure in any given area in the ocean.